In vitro evaluation of the toxicity and underlying molecular mechanisms of Janus Fe3O4‐TiO2 nanoparticles in human liver cells. Issue 10 (11th August 2018) - Su, Hong; Li, Zhou; Lazar, Lissy; Alhamoud, Yasmin; Song, Xin; Li, Juan; Wang, Yafei; Fiati kenston, Samuel Selorm; Lqbal, Muhammad Zubair; Wu, Aiguo; Li, Zhen; Hua, Qihang; et al.
Abstract: Recent studies show that Janus Fe3 O4 ‐TiO2 nanoparticles (NPs) have potential applications as a multifunctional agent of magnetic resonance imaging (MRI) and photodynamic therapy (PDT) for the diagnosis and therapy of cancer. However, little work has been done on their biological effects. To evaluate the toxicity and underlying molecular mechanisms of Janus Fe3 O4 ‐TiO2 nanoparticles, an in vitro study using a human liver cell line HL‐7702 cells was conducted. For comparison, the Janus Fe3 O4 ‐TiO2 NPs parent material TiO2 NPs was also evaluated. Results showed that both Fe3 O4 ‐TiO2 NPs and TiO2 NPs decreased cell viability and ATP levels when applied in treatment, but increased malonaldehyde (MDA) and reactive oxygen species (ROS) generation. Mitochondria JC‐1 staining assay showed that mitochondrial membrane permeability injury occurred in both NPs treated cells. Cell viability analysis showed that TiO2 NPs induced slightly higher cytotoxicity than Fe3 O4 ‐TiO2 NPs in HL7702 cells. Western blotting indicated that both TiO2 NPs and Fe3 O4 ‐TiO2 NPs could induce apoptosis, inflammation, and carcinogenesis related signal protein alterations. Comparatively, Fe3 O4 ‐TiO2 NPs induced higher signal protein expressions than TiO2 NPs under a high treatment dose. However, under a low dose (6.25 μg/cm 2 ), neither NPs had any significant toxicity on HL7702 cells. In addition, our results suggest both Fe3 O4 ‐TiO2 NPs and TiO2 NPs could induce oxidative stress and have a potential carcinogenetic effect in vitro. Further studies are needed to elaborate the detailed mechanisms of toxicity induced by a high dose of Fe3 O4 ‐TiO2 NPs.